Exchange rates, capital, output and debt when nominal interest rates are policy parameters - Sinclair, P. J. N. (Economic & Social Studies, 1990)
Recent years have witnessed a growing number of attempts to reduce inflation by a policy of raising nominal interest rates. Since 1988, such measures have been particularly pronounced in Australia, Canada and the United Kingdom. It is important to ask how higher interest rates can help to lower inflation, what factors determine the speed and reliability of the mechanisms involved, and, above all, what the side-effects of such policies may be. The purpose of this paper is to explore various mechanisms through which nominal interest rates may affect the course of inflation, in the context of an open economy model where exchange rates are freely floating. The main focus of attention is upon how output and income react, in the short run and the long, to a change in the nominal rate of interest.
Keywords: exchange rates; debt; capital; interest rates